Ionospheric effects of volcanic eruptions - de Ragone, Argelia H. C. (2004)
Ionospheric effects of Mount Pinatubo volcanic eruption in June 1991 were recorded on 1-minute interval soundings made by stations north of the volcano. Disturbances characterized by quasi-periodic wavelike trains were detected. They were attributed to gravity waves generated by the eruption, and its characteristics were determined. We search for similar ionospheric disturbances caused by volcanic eruptions in North and South America, based on hourly F2 critical frequency (foF2) and F layer virtual height (h?F) data. The study was carried out for quiet magnetic activity levels. All eruptions reached the Pinatubo intensity. A decrease of foF2 and of its amplitude of variation, and an increase of h?F in relation to their values during the day before and after the eruption were detected in some cases. In other cases the disturbance was detected for only one parameter, or for none. The absence of disturbances in the hourly records could be due to the lack of coincidence between the maximum departures of the parameters from the normal situation, and the recording time of the parameter. The observed disturbances are correlated with the eruption intensity.